2018
DOI: 10.1016/j.dnarep.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of H3 and H4 nucleosome tails on structure and dynamics of a lesion-containing DNA: Binding of a displaced lesion partner base to the H3 tail for GG-NER recognition

Abstract: How DNA lesions in nucleosomes are recognized for global genome nucleotide excision repair (GG-NER) remains poorly understood, and the roles that histone tails may play remains to be established. Histone H3 and H4 N-terminal tails are of particular interest as their acetylation states are important in regulating nucleosomal functions in transcription, replication and repair. In particular the H3 tail has been the focus of recent attention as a site for the interaction with XPC, the GG-NER lesion recognition fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Notably, this modeling does not account for the dynamic histone tails that could also modulate binding of repair enzymes. It is intriguing to consider that the H2B and H4 tails near site 97 may contribute to the unexpectedly low amount of excision by AAG at this location, as histone tails have been shown to alter the structure and dynamics of damaged DNA. , The H2B tail is also in close proximity to site 102 and may account for the unexpected lower levels of εA excision by AAG. However, the unexpectedly high excision at site 105 indicates that the microenvironment generated by the H2B tail may have more complex and nuanced effects that include local structural changes, sterics, and electrostatics.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this modeling does not account for the dynamic histone tails that could also modulate binding of repair enzymes. It is intriguing to consider that the H2B and H4 tails near site 97 may contribute to the unexpectedly low amount of excision by AAG at this location, as histone tails have been shown to alter the structure and dynamics of damaged DNA. , The H2B tail is also in close proximity to site 102 and may account for the unexpected lower levels of εA excision by AAG. However, the unexpectedly high excision at site 105 indicates that the microenvironment generated by the H2B tail may have more complex and nuanced effects that include local structural changes, sterics, and electrostatics.…”
Section: Discussionmentioning
confidence: 99%
“…These potential synergistic tail−tail interactions are not unexpected as computational studies have shown that the acetylation of the H4 tail impacts the ability of the H3 tail to interact with other proteins. 55 Similarly, the maximum shift from position 65 to position 64, making it a more OUT lesion, in the gH3 NCP does not confer enhanced εA excision. In contrast, the gH2B NCPs show a small enhancement of activity while retaining the same maximum at position 65 seen in native NCPs.…”
Section: ■ Discussionmentioning
confidence: 94%
“…The H4 tail, important for internucleosomal interactions, in this region may undergo a conformational change in the absence of the H3 tail that inhibits AAG binding or excision activity. These potential synergistic tail–tail interactions are not unexpected as computational studies have shown that the acetylation of the H4 tail impacts the ability of the H3 tail to interact with other proteins . Similarly, the maximum shift from position 65 to position 64, making it a more OUT lesion, in the gH3 NCP does not confer enhanced εA excision.…”
Section: Discussionmentioning
confidence: 98%
“…This work constitutes a proof of concept for studying DNA-protein interactions within a nucleosome core particle harboring multiple sites damage, and our protocol sets the grounds for further studies of Ap reactivity upon histone post-translational modifications 31 and the role of histone tail in DNA repair proteins recruitment. 32…”
Section: Extrahelicity Of the Lesion Sites (%)mentioning
confidence: 99%